2015
DOI: 10.1038/srep08056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the enzyme and PCR conditions on the quality of high-throughput DNA sequencing results

Abstract: Library preparation protocols for high-throughput DNA sequencing (HTS) include amplification steps in which errors can build up. In order to have confidence in the sequencing data, it is important to understand the effects of different Taq polymerases and PCR amplification protocols on the DNA molecules sequenced. We compared thirteen enzymes in three different marker systems: simple, single copy nuclear gene and complex multi-gene family. We also tested a modified PCR protocol, which has been suggested to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…For instance, template concentration, bias against high GC templates, template switching, and polymerase errors may contribute to errors in downstream steps [2729]. These previous studies indicated that these bias and errors can be minimized by using the minimum number of amplification cycles required to form products and defining the optimal template concentration in the PCR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, template concentration, bias against high GC templates, template switching, and polymerase errors may contribute to errors in downstream steps [2729]. These previous studies indicated that these bias and errors can be minimized by using the minimum number of amplification cycles required to form products and defining the optimal template concentration in the PCR reaction.…”
Section: Resultsmentioning
confidence: 99%
“…If introduced during early cycles of the PCR, these can potentially exceed the frequency of real alleles. The choice of the DNA polymerase and specifically its error rate has a profound impact on the quality of sequencing data [Brandariz‐Fontes et al, ]. Different enzymes vary in their processivity and specificity, especially in the presence of templates of inferior quality and/or with low‐copy number [Arezi et al, ; Moretti et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well understood that different PCR conditions and different DNA polymerases will have different amplification biases and errors (Brandariz-Fontes et al 2015), which could impact the results of DNA metabarcoding studies. Ideally, a single enzyme and set of amplification conditions would be used across all DNA metabarcoding studies, but due to the large variation in sample media, primers, and taxa of interest, this is not possible.…”
Section: Pcr Conditions and Dna Polymerasesmentioning
confidence: 99%